Optimal operation of multi-reservoir systems for increasing power generation using a seagull optimization algorithm and heading policy - Ehteram M.; Banadkooki F.B.; Fai C.M.; Moslemzadeh M.; Sapitang M.; Ahmed A.N.; Irwan D.; El-Shafie A. (Elsevier Ltd, 2023)
Decision making; Natural language processing systems; Bat algorithms; Heading policy; Multi-reservoir operation; Multi-reservoir systems; Optimization algorithms; Power- generations; Salp swarms; Seagull optimization algorithm; Swarm algorithms; Two-point; Optimization